Sequence Variants of ADIPOQ and Association with Type 2 Diabetes Mellitus in Taiwan Chinese Han Population - Ming-Kai Tsai; Hui-Min David Wang; Jeng-Chuan Shiang; I-Hung Chen; Chih-Chiang Wang; Ya-Fen Shiao; Wen-Sheng Liu; Tai-Jung Lin; Tsung-Ming Chen; Ya-Huey Chen (The Scientific World Journal)
Diabetes is a serious global health problem. Large-scale genome-wide association studies identified loci for type 2 diabetes mellitus (T2DM), including adiponectin (ADIPOQ) gene and transcription factor 7-like 2 (TCF7L2), but few studies clarified the effect of genetic polymorphisms of ADIPOQ and TCF7L2 on risk of T2DM. We attempted to elucidate association between T2DM and polymorphic variations of both in Taiwan’s Chinese Han population, with our retrospective case-control study genotyping single nucleotide polymorphisms (SNPs) in ADIPOQ and TCF7L2 genes both in 149 T2DM patients and in 139 healthy controls from Taiwan. Statistical analysis gauged association of these polymorphisms with risk of T2DM to show ADIPOQ rs1501299 polymorphism variations strongly correlated with T2DM risk (P=0.042), with rs2241766 polymorphism being not associated with T2DM (P=0.967). However, both polymorphisms rs7903146 and rs12255372 of TCF7L2 were rarely detected in Taiwanese people. This study avers that ADIPOQ rs1501299 polymorphism contributes to risk of T2DM in the Taiwanese population.